Endocrine Disruptors: Focus on the Adrenal Cortex - Pötzl, Benedikt; Kürzinger, Lydia; Stopper, Helga; Fassnacht, Martin; Kurlbaum, Max; Dischinger, Ulrich (Hormone and Metabolic Research, 2024)
Endocrine-disrupting chemicals (EDCs) are exogenous substances known to interfere with endocrine homeostasis and promote adverse health outcomes. Their impact on the adrenal cortex, corticosteroids and their physiological role in the organism has not yet been sufficiently elucidated. In this review, we collect experimental and epidemiological evidence on adrenal disruption by relevant endocrine disruptors. In vitro data suggest significant alterations of gene expression, cell signalling, steroid production, steroid distribution, and action. Additionally, morphological studies revealed disturbances in tissue organization and development, local inflammation, and zone-specific hyperplasia. Finally, endocrine circuits, such as the hypothalamic-pituitary-adrenal axis, might be affected by EDCs. Many questions regarding the detection of steroidogenesis disruption and the effects of combined toxicity remain unanswered. Not only due to the diverse mode of action of adrenal steroids and their implication in many common diseases, there is no doubt that further research on endocrine disruption of the adrenocortical system is needed.
Keywords: endocrine disrupting chemicals; adrenal gland; corticosteroids; HPA axis; bisphenol A